Coeliac disease–associated disorders and survival. Issue 9 (September 1994) - Collin, P; Reunala, T; Pukkala, E; Laippala, P; Keyriläinen, O; Pasternack, A
Abstract : The associated diseases in 335 coeliac patients diagnosed 1980-90 were compared with age and sex matched control patients with various gastrointestinal symptoms. Endocrine disorders were found in 11.9% of coeliac and 4.3% of control patients (p = 0.0003). Coeliac patients had insulin dependent diabetes mellitus significantly (p = 0.0094) more often (5.4%) than control patients (1.5%). connective tissue diseases were found in 7.2% of coeliac and in 2.7% of control patients (p = 0.011). Sjögren's syndrome occurred in 3.3% of coeliac patients and in 0.3% of controls (p = 0.0059). Autoimmune thyroid diseases were found in 5.4% and asthma in 3.6% of coeliac patients, but also in 2.7% and 3.6%, respectively, among control patients. The incidences of malignant diseases and the survival rate in coeliac patients were compared with those in the Finnish population. Ten coeliac patients developed a cancer during the follow up (mean 5.3 years, range 1-12) but none had a lymphoma. The risk of malignant diseases in coeliac patients did not differ from that in the Finnish population in general. Eleven coeliac patients died during the follow up. The five year survival rates of coeliac patients did not differ from those in the general population. At least 83% of the coeliac patients adhered strictly to the gluten free diet, which may explain the favourable outcome.